SOURCES OF INVESTMENT FINANCING AND THEIR IMPACT ON ECONOMIC GROWTH OF THE REPUBLIC OF SERBIA - Tešić, Aleksandra; Ilić, Dragan; Tepavac, Rajko (Economics of Agriculture, 2013)
The aim of this paper is to point out to the important issues of investments in Serbia, with particular focus on the fact that investments can never be the objective but only the generator of economic growth, its pace, development structure and stability. With this in mind and depending on economic cycle and its phases, the connection between the amount and structure of investments and economic growth is studied as well as the investment behavior as part of global demand and spending in the function of total consumption. In the analysis of investments and their financing effects on economic growth of Serbia, relevant studies and articles were used, together with the reports and publications of competent institutions. The results of the analysis indicate the crisis of investments and their financing method in Serbia which has been accumulating for many years now, with an increasing foreign debt arising from predominantly external investment financing. The main conclusion is that for every economy, programming and monitoring of necessary investments, their economic, technical and regional structure as well as financing system is of strategic importance.